E-business. - Holden, Greg, ....-; Belew, Shannon, ....- (Hoboken : Wiley, 2009)
For anyone thinking about starting an online business, this resource provides all the steps needed to take an idea and turn it into reality. Wiley Pathways E-Business begins by discussing the legal considerations involved in launching the business as well as tips for acquiring the necessary financing. It also delves into the techniques to follow for operating the e-business, including selecting the right products, managing inventory, creating a marketing plan, and more. The book then covers how to create a secure Web site that can track customer data. Part 1: Getting Started in E-Business. 1. An Introduction to E-Business. 2. The Law, Ethics, and Consumer Policies. 3. Planning an E-Business. 4. Financing and Launching an E-Business. 5. Accounting and Taxes. Part 2: Operating an E-Business. 6. Online Revenues and Payments. 7. Products, Inventory, and Fulfillment. 8. Marketing an E-Business. 9. Effectively Using Search Engines. 10. E-Business Customer Service. Part 3: Creating and Operating a Website. 11. Equipment, Software, and Web Hosting. 12. Successful Web Site Design. 13. Tracking and Analyzing Customer Data. 14. E-Business Security. Glossary. Credits. Index.
Keywords: E-business.; E-commerce.